EFFECT OF TYPE2 DIABETES ON EYE DISEASES (LENOPATHY, GLAUCOMA, RETINOPATHY AND OPTIC NEUROPATHY) - Estabraq Mufid Hamid Rashid; Zainab Ibrahim Harat Khalaf; Mariam Ahmed Abd alghfer Muscat; Omar Hammed Saleh Ibrahim; Haider Jassim Mohammed Hussein (Journal of Medical Genetics and Clinical Biology, 2024)
Awareness about diabetic eye complications and regular eye examinations plays an important role in avoiding blindness. Objective: To evaluate the level of awareness and knowledge about diabetic eye diseases among diabetic patients. Patients attending Ibn al-Haytham Teaching Hospital for Eye Diseases in Baghdad. Method: This is a cross-sectional study including a sample of 115 diabetic patients attending this center during the treatment period. The period is from 2023/8/15_2023/10/25. To achieve the objectives of the study, a closed study was conducted. A questionnaire that includes different variables related to diabetes awareness for each of them. The authors filled out the questionnaire during interviews with patients.